INTERACTION ON COMMENTS AS COMMUNICATION IN DIGITAL ERA - I Gusti Ngurah Parthama; Ni Luh Kade Yuliani Giri (Politeknik Negeri Jakarta, 2024)
The research is aimed in describing the use of language and its interaction on comments section as part of communication in digital era. interaction with written language is part of digital communication today. Interaction via comments play an important role through many platforms of digital. People are able to interact with others and show their opinions, argumentations, questions, judgments, and others in social media with language. The data source was taken from interaction of language in social media Facebook. The data was the language used by the internet users in delivering their comments for specific information in the main text. The method of collecting data was documentation and it was supported by reading in detail, note taking, and classifying. The analysing data was qualitative. It is the selected data that was analysed descriptively based on theory and studies for language and communication in digital era. The findings show that comments have dominantly sentiment negative to the information given. The negative sentiments are delivered with some mode of communication like giving opinions, allegations, and appraisals. Those comments can also be identified due to its relation to the main text. It is divided into its inline or not within the topic of main text